Influence of hysteroscopic metroplasty on reproductive outcome in patients with infertility and recurrent pregnancy loss - Tofoski, Gligor; Antovska, Vesna (Walter de Gruyter GmbH/Macedonian Academy of Sciences and Arts, 2014)
Patients with congenital uterine anomalies (CUA) have decreased reproductive potential and an unfavourable reproductive outcome compared to the population with normal uterine cavity. Patients with untreated CUA have a higher abortion rate, higher foetal loss rate and decreased live birth rate. Hysteroscopic metroplasty is a standard, safe and minimally invasive method for the treatment of correctible types of congenital uterine anomalies. The aim of the study was to analyse the reproductive outcome in certain groups of patients with CUA and infertility, before and after hysteroscopic metroplasty.